2016
DOI: 10.1097/tp.0000000000001141
|View full text |Cite|
|
Sign up to set email alerts
|

High-Fat Diet–Induced Obesity Enhances Allograft Rejection

Abstract: Background Obesity promotes a state of low-grade inflammation that exacerbates chronic inflammatory diseases such as asthma and inflammatory bowel disease. In transplantation, the survival of organs transplanted into obese patients is reduced compared to allografts in lean recipients. However, whether this is due to increased alloimmunity remains to be addressed conclusively. Methods We used a mouse model of high fat diet (HFD)-induced obesity and assessed immune responses to allogeneic stimulation in vitro,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 44 publications
2
27
2
1
Order By: Relevance
“…Thus, overall antigen presentation in hyperlipidemic mice remains unchanged or slightly impaired. These results differ from those of a recent study in which APCs were found to have greater stimulatory capacity if animals were fed an HFD for over 12 weeks, when obesity-induced inflammation is prominent (53). Also, in this study, control mice were fed a nutrient-matched low-fat diet, rather than normal chow, possibly revealing a lower stimulatory capacity of control APCs.…”
Section: Impact Of Pollutants On Graft Outcomecontrasting
confidence: 56%
See 1 more Smart Citation
“…Thus, overall antigen presentation in hyperlipidemic mice remains unchanged or slightly impaired. These results differ from those of a recent study in which APCs were found to have greater stimulatory capacity if animals were fed an HFD for over 12 weeks, when obesity-induced inflammation is prominent (53). Also, in this study, control mice were fed a nutrient-matched low-fat diet, rather than normal chow, possibly revealing a lower stimulatory capacity of control APCs.…”
Section: Impact Of Pollutants On Graft Outcomecontrasting
confidence: 56%
“…Thus, hyperlipidemia leads to accelerated rejection independently of obesity and hyperglycemia. Accelerated rejection of minor antigen-mismatched cardiac grafts was also observed in mice on an HFD compared with mice on a nutrient-matched low-fat diet (53). Together, these data point to a role for hyperlipidemia in transplant rejection.…”
Section: R E V I E W S E R I E S : T R a N S P L A N Tat I O Nsupporting
confidence: 51%
“…We found that rejection of HY-mismatched skin was significantly accelerated in HFD as compared to CD female recipients (Figure 1E) (Molinero et al., 2016). Activation of CD4 + T cells and their localization to the graft are known to be instrumental to rejection in this system (Chen et al., 2003).…”
Section: Resultsmentioning
confidence: 72%
“…Thus, rejection of heart grafts is accelerated independently of obesity, hyperglycemia, high fat diet and ApoE−/− mutation status, but is correlated with degree of hyperlipidemia. Accelerated rejection of cardiac grafts in mice on a high fat diet has recently been confirmed by a study performed comparing mice on a high fat diet with mice given a low fat diet (62). Together, these data point to a role for hyperlipidemia in transplant rejection.…”
Section: Modeling Effects Of Hyperlipidemia On Transplant Survival Inmentioning
confidence: 90%